The Effect of Six-Week Neuromuscular Training and Calcium-Magnesium-Zinc Supplementation on Balance and Electromyographic Activity of the Lower Limb Muscles among Elite Taekwondo Athletes - Babak Esmealy; Leyla Esmealy; Azam Zarneshan (International Journal of Nutrition Sciences)
Background: Neuromuscular coordination and the ability to maintain one-legged balance are two important prerequisites for successful taekwondo performance. This study investigated the effect of six weeks neuromuscular training (NMT) and calcium-magnesium-zinc (Ca-Mg-Zn) supplementation on balance and electromyographic (EMG) activityof lower limb muscles among taekwondo athletes.Methods: In a randomized control trial from September to December 2023 in the Regional Sports Concussion Center, sixty elite taekwondo athletes were enrolled and assigned to four fifteen-member groups, namely the control, Ca-Mg-Zn, NMT, and Ca-Mg-Zn+NMT groups. NMT was performed three times a week for sixty minutes for sixconsecutive weeks. Between-group and within-group analyzes were performed to determine differences in demographics, static, control of dynamic balance, and EMG between the 4 groups.Results: The mean value of displacement of the center of pressure decreased in all groups. There were significant differences between the groups in terms of static and dynamic balance with eyes open. There was no significant difference between the groups in the mean value of dynamic balance with eyes closed. EMG activity of the tibialis anterior, rectus and biceps femoris muscles 100-200 milliseconds after first contact did not change significantly between the groups, while the effect size of the Ca-Mg-Zn+NMT intervention on the increase in EMG activity and balance control after the intervention was higher than other groups.Conclusion: The combination of NMT and Ca-Mg-Zn supplementation was more effective than NMT and Ca-Mg-Zn supplementation to improve static and dynamic balance and EMG activity in taekwondo athletes.